IMPLEMENTATION OF ISLAMIC AQEEDAH BASED CURRICULUM - Afifah, Neela; Suriansyah, Ahmad; Aslamiah, Aslamiah (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
Curriculum implementation is an application of concepts in the form of curriculum documents into learning process. This study aims to identify and describe the management curriculum, evaluation, and other factors that affect the implementation of Islamic Aqeedah based curriculum. This research uses qualitative approach. The object of is Islamic Aqeedah based curriculum and the subjects are teachers and students used triangulation data with cross-site data analysis. The results of the study show that learning is designed by making curriculum guidelines, academic calendars, determining themes, learning schedules and daily activity. Organization is implemented by making organizational structure and daily task distribution. Learning implementation uses discovery learning which is called by 'talqiyyan fikriyyan' method by integrating all knowledges into Islamic Aqeedah. The form of controllings are supervision. Learning evaluation uses connecting books or diaries. The factors that influence the implementation of the curriculum are teachers, parents, students, environment and government.